PML and PML-like exonucleases restrict retrotransposons in jawed vertebrates. Issue 7 (13th March 2023) - Mathavarajah, Sabateeshan; Vergunst, Kathleen L; Habib, Elias B; Williams, Shelby K; He, Raymond; Maliougina, Maria; Park, Mika; Salsman, Jayme; Roy, Stéphane; Braasch, Ingo; Roger, Andrew J; Langelaan, David N; et al.
Abstract: We have uncovered a role for the promyelocytic leukemia ( PML ) gene and novel PML-like DEDDh exonucleases in the maintenance of genome stability through the restriction of LINE-1 (L1) retrotransposition in jawed vertebrates. Although the mammalian PML protein forms nuclear bodies, we found that the spotted gar PML ortholog and related proteins in fish function as cytoplasmic DEDDh exonucleases. In contrast, PML proteins from amniote species localized both to the cytoplasm and formed nuclear bodies. We also identified the PML-like exon 9 ( Plex9 ) genes in teleost fishes that encode exonucleases. Plex9 proteins resemble TREX1 but are unique from the TREX family and share homology to gar PML. We also characterized the molecular evolution of TREX1 and the first non-mammalian TREX1 homologs in axolotl. In an example of convergent evolution and akin to TREX1, gar PML and zebrafish Plex9 proteins suppressed L1 retrotransposition and could complement TREX1 knockout in mammalian cells. Following export to the cytoplasm, the human PML-I isoform also restricted L1 through its conserved C-terminus by enhancing ORF1p degradation through the ubiquitin-proteasome system. Thus, PML first emerged as a cytoplasmic suppressor of retroelements, and this function is retained in amniotes despite its new role in the assembly of nuclear bodies.